2023
DOI: 10.3390/ijms242216165
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Chitosan Induces a Biochemical and Molecular Response in Coffea arabica during Infection with Hemileia vastatrix

Julio César López-Velázquez,
Soledad García-Morales,
Gloria Paola López-Sánchez
et al.

Abstract: The coffee industry faces coffee leaf rust caused by Hemileia vastratix, which is considered the most devastating disease of the crop, as it reduces the photosynthetic rate and limits productivity. The use of plant resistance inducers, such as chitosan, is an alternative for the control of the disease by inducing the synthesis of phytoalexins, as well as the activation of resistance genes. Previously, the effect of chitosan from different sources and physicochemical properties was studied; however, its mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This activation enhances the plant's protection against common vineyard diseases, such as powdery and downy mildew [41,42]. Similar outcomes have been observed in diverse plant species, including tomato and Coffea arabica [44,45], highlighting the importance on understanding the impact of PRIs on plants.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This activation enhances the plant's protection against common vineyard diseases, such as powdery and downy mildew [41,42]. Similar outcomes have been observed in diverse plant species, including tomato and Coffea arabica [44,45], highlighting the importance on understanding the impact of PRIs on plants.…”
Section: Discussionmentioning
confidence: 55%
“…Although PAL did not exhibit significant differences in gene expression levels, we verify that STS1 showed significant differences between production modes in 'Alicante Bouschet', with a tendency towards significance in 'Trincadeira'. A previous study carried out on a 50-year-old vineyard in Greece reported that chitosan and abscisic acid induce phenylpropanoid gene expression, including PAL [44]; an increase of expression and enzyme activity of both PAL and STS1 was verified using a suspension of the epiphytic yeast Aureobasidium pullulans, which was potentially used as a PRI [45].…”
Section: Discussionmentioning
confidence: 95%